Failure to Redose Antibiotic Prophylaxis in Long Surgery Increases Risk of Surgical Site Infection - Nongyao Kasatpibal (2018)
© Copyright 2017, Mary Ann Liebert, Inc. Background: Antibiotic prophylaxis is a key component of the prevention of surgical site infection (SSI). Failure to manage antibiotic prophylaxis effectively may increase the risk of SSI. This study aimed to examine the effects of antibiotic prophylaxis on SSI risk. Methods: A retrospective cohort study was conducted among patients having general surgery between May 2012 and June 2015 at the University of Washington Medical Center. Peri-operative data extracted from hospital databases included patient and operation characteristics, intra-operative medication and fluid administration, and survival outcome. The effects of antibiotic prophylaxis and potential factors on SSI risk were estimated using multiple logistic regression and were expressed as risk ratios (RRs). Results: A total of 4,078 patients were eligible for analysis. Of these, 180 had an SSI. Mortality rates within and after 30 days were 0.8% and 0.3%, respectively. Improper antibiotic redosing increased the risk of SSI (RR 4.61; 95% confidence interval [CI] 1.33-15.91). Other risk factors were in-patient status (RR 4.05; 95% CI 1.69-9.66), smoking (RR 1.63; 95% CI 1.03-2.55), emergency surgery (RR 1.97; 95% CI 1.26-3.08), colectomy (RR 3.31; 95% CI 1.19-9.23), pancreatectomy (RR 4.52; 95% CI 1.53-13.39), proctectomy (RR 5.02; 95% CI 1.72-14.67), small bowel surgery (RR 6.16; 95% CI 2.13-17.79), intra-operative blood transfusion > 500 mL (RR 2.76; 95% CI 1.45-5.26), and multiple procedures (RR 1.40; 95% CI 1.01-1.95). Conclusions: These data demonstrate that failure to redose prophylactic antibiotic during long operations increases the risk of SSI. Strengthening a collaborative surgical quality improvement program may help to eradicate this risk.